Trabalhadores das plataformas digitais de prestação de serviços : proteção social como forma de inclusão no desenvolvimento econômico tecnológico - Peixoto, Aguimar Martins (2022)
This is the present master's thesis on the investigation of working conditions and the legal system to be applied to workers in the so-called ³FURZGZRUNLQJ´ or ³Gig Economy´, which is the reinvention of capital via digital work platforms, for the exploitation of the workforce. Before focusing on work through digital platforms, we carried out a study on industrial revolutions, which left indelible marks on societies, and on the world of work specifically. We have tried to make clear the new social cycles marked by revolutions, which we know if they are really transforming events when three types of revolutionary events occur in History, coincidentally: the discovery of new energy sources, a new division of labor and a new organization of power, as they bring with them new epistemology, new ways of seeing progress and the world. We focus on classical liberalism and the advent of neoliberalism and its strategies, in order to base our criticism on how the present study could help digital platform workers achieve decent working conditions. We approach technological innovations, as a stage for human work, built by digital platforms, which originated and are supported by the fourth industrial revolution or industry 4.0. Still in this sense, we advocate that service providers who identify themselves as self-employed or partners of the platforms that intermediate and benefit from their activities may be competing with themselves, in the illusion of self-entrepreneurship, when they are nothing more than workers economically dependent on the user of their services, even though they have freedom of work, and that this freedom is nothing more than a new component of legal subordination, in new clothes. We aligned in two sub-items the performance of the economic freedom law in Brazil, in its objectives of meeting the desires of capital so that there is greater or no labor regulation or State-judge intervention in civil contracts, as a way of increasing profits and reducing legal protection for workers, while eliminating the social function of contracts. In opposition to the capitalist objectives of the platforms, we formulate the sub-item of Social Justice, which it is expected that it will be able to compose the different interests between capital and labor. In chapter II we define digital platforms, intensifying the focus on service platforms, specifically those that make up the Gig Economy and its workers, the specific object of this research. We researched how the workers of the sharing economy platforms, another name for the gig economy, organize themselves collectively, and how they manage to identify themselves in the legal gray area between autonomous and dependent subordinate work, through national and foreign jurisprudence. Still in the jurisprudence and in the doctrine we find the resignification of the legal subordination, in the new context of the algorithmic subordination. We analyze how Foreign Law has been treating workers on digital platforms, and how Brazilian law has been disciplining the same worker. Finally, in chapter III, we discuss the fundamental human social rights applied to every worker, regardless of whether it is formal or informal, and the challenges for the legal realization of decent work for all workers on digital platforms.